Voice into acting integrating voice and the Stanislavski approach - Gutekunst, Christina; Gillett, John (Methuen Drama, 2021)
"How can actors bridge the gap between themselves and the text and action of a script, integrating fully their learned vocal skills? How do we make an imaginary world real, create the life of a role, and fully embody it vocally and physically so that voice and acting become one? Christina Gutekunst and John Gillett unite their depth of experience in voice training and acting to create an integrated and comprehensive approach informed by Stanislavski and his successors - the acting approach widely taught to actors in drama schools throughout the world. This updated edition contains: a new section on vocal embodiment of actions, new findings from neuroscience as evidence of the science behind the approach, more exercises and warm-up routines for training, pre-rehearsal and pre-performance.